Reference intervals for selected haematological and biochemical parameters among apparently healthy adults in different eco-geographical zones in Ghana - Abbam, Gabriel (PLoS One, 2021)
BACKGROUND: Due to the influence of gender, race/genetics, age, lifestyle habits and geography on the references intervals (RIs), the Clinical and Laboratory Standards Institute (CLSI) recommends the determination of population-specific RIs. Ghana continues to depend on pre-established RIs from other countries which poses the risk of misdiagnoses and wrong treatment. This study presents the haemato-biochemical RIs from four eco-geographical zones in Ghana. METHODS: In this population-based cross-sectional study, a total of 1227 randomly selected healthy voluntary blood donors from the four eco-geographic zones (Coastal Savannah, Rain Forest, Savannah and Transitional) were enrolled and screened. Based on the CLSI Guidance Document C28A2992, the data of eligible participants were used to non-parametrically determine the RIs for the haemato-biochemical parameters at the 2.5(th) and 97.5(th) percentiles. Comparison of analytes by gender was done by Wilcoxon rank sum test and eco-geographic differences were assessed using the Kruskal-Wallis with the Dunn post hoc multiple comparison tests. RESULTS: There were statistically significant differences in most of the haematological parameters (RBC, Hb, HCT, MCV, PLT, WBC; p-values <0.0001 and MCH; p-value = 0.007), and biochemical analytes (Urea, Cr, Trig, HDL-C, AST, ALT, ALP, GGT, BID, BIT, Prot-T and Albumin; p-values <0.0001) based on gender. Significant inter eco-geographic (intra-population) variations and substantial differences between the established RI and the RIs accompanying the analyzers used were also observed. CONCLUSION: This study reports significant inter-sex and inter-geographical differences in haemato-biochemical RIs in Ghana as well as differences in RIs with both the RIs accompanying the analyzers and those of other countries. Determining RIs representative of populations and including them in the report systems of laboratories to ensure effective and efficient healthcare service delivery is thus recommended.